Lithium-rich lithium ferrite slurry as well as preparation method and application thereof

By mixing lithium lithium ferrate with solvent and thickener to make a stable slurry, the problem of poor air stability is solved, and the battery performance and convenience of storage and transportation are improved.

CN119764448AInactive Publication Date: 2025-04-04CHANGSHA MINING & METALLURGY INST TESTING TECH CO LTD

Patent Information

Application Number
CN202411848768.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The poor air stability of lithium lithium ferrate leads to a decrease in the specific capacity of the material and reacts with the positive electrode binder PVDF, causing gels in the pulping process, limiting its large-scale application.

Method used

Lithium-rich lithium ferrate is mixed with solvent and thickener to make a stable slurry, which is evenly dispersed by mechanical stirring, reducing sensitivity to air and moisture.

Benefits of technology

It effectively improves the use effect of lithium-rich lithium ferrate and the convenience of storage and transportation, avoids gel problems, and improves the stability of the positive electrode slurry and battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764448A_ABST
    Figure CN119764448A_ABST
Patent Text Reader

Abstract

The invention discloses lithium-rich lithium ferrite slurry and a preparation method and application thereof.The lithium-rich lithium ferrite slurry is composed of lithium-rich lithium ferrite, a thickening agent and a solvent, in a dry environment, lithium-rich lithium ferrite powder, the thickening agent and the solvent are weighed, the thickening agent is mechanically stirred and dissolved in the solvent, then the lithium-rich lithium ferrite is added, stirring is conducted under the vacuum condition, and a uniform suspension is obtained; according to the lithium-rich lithium ferrite slurry prepared by the method, the sensitivity of lithium-rich lithium ferrite to air and moisture is effectively reduced, and the problem that the lithium-rich lithium ferrite is easy to lose efficacy is solved. When in use, the lithium-rich lithium ferrite is added after the raw materials of the positive electrode material are dispersed and before the step of adjusting the viscosity, so that the problem of slurry gel during positive electrode slurrying caused by premature reaction between the lithium-rich lithium ferrite and the binder PVDF in the positive electrode slurry is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium supplement additives and lithium ion battery applications, and in particular relates to a lithium-rich lithium ferrite slurry and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used in various portable electronic devices, electric vehicles and other fields due to their high energy density, long cycle life and environmental protection. However, lithium-ion batteries will experience irreversible lithium loss during the initial charge and discharge process and during the cycle, which causes the actual available capacity of the battery to be lower than the theoretical value. Lithium supplements can compensate for this loss by providing additional lithium sources, thereby improving the energy density and cycle energy of the battery. There are many types of lithium supplements currently being studied and reported, among which lithium-rich lithium iron oxide (Li5FeO4) is considered to be the lithium supplement with the best application prospects because of its high specific capacity (867mAh / g), suitable delithiation voltage (3.5-4.7V) and low cost.

[0003] In the existing technology, lithium supplements are usually added directly to the positive electrode slurry in the form of powder during pulping. However, lithium-rich lithium ferrite has extremely poor air stability. When it comes into contact with air at room temperature, lithium compounds will be produced, which will reduce the specific capacity of the material. At the same time, the lithium compounds produced are alkaline and will react with the positive electrode binder PVDF, causing gelation during the pulping process. In addition, lithium-rich lithium ferrite is directly used in the form of powder for positive electrode pulping, which is prone to problems such as uneven mixing in a short period of time or low production efficiency due to long-term mixing. The above defects limit the storage, transportation and use of lithium-rich lithium ferrite, greatly affecting its large-scale application. Existing solutions often reduce the problem of lithium supplements being sensitive to air by coating the material, such as Chinese patent document CN115642232A and patent CN117199276A. Although certain effects have been achieved, there are problems of complex process and high cost. Summary of the invention

[0004] In order to overcome the problems in the prior art, the present invention provides a lithium-rich lithium iron phosphate slurry and a preparation method and application thereof, which solves the problem that lithium-rich lithium iron phosphate is easy to fail, and the preparation process is simple and low-cost, which not only saves energy and time in the preparation process, but also reduces production costs.

[0005] In order to solve the above technical problems, the technical solution proposed by the present invention is: The invention provides a lithium-rich ferrite slurry, which is composed of lithium-rich ferrite, a thickener and a solvent. The solvent is a solvent used in preparing positive electrode slurry.

[0006] In the present invention, lithium-rich iron oxide is made into a stable slurry with a solvent and a thickener, and the lithium-rich iron oxide is uniformly dispersed in a mixed solution of the solvent and the thickener by mechanical stirring, and the thickener is used as a stabilizer to form a stable lithium-rich iron oxide slurry. The slurry not only dilutes the concentration of lithium-rich iron oxide but also isolates air and moisture, greatly reducing the sensitivity of lithium-rich iron oxide to air and moisture.

[0007] As an optional embodiment, in the lithium-rich lithium ferrite slurry provided by the present invention, the mass ratio of the lithium-rich lithium ferrite, the thickener and the solvent is 90-99.5:0.5-10:25-200.

[0008] Furthermore, it is preferably 90-98:2-10:50-100.

[0009] In the present invention, controlling the mass ratio of lithium-rich lithium ferrite, thickener and solvent within the above range is conducive to ensuring that the slurry is within the optimal viscosity range. Otherwise, if the viscosity is too low, the slurry is unstable and easy to stratify, and if the viscosity is too high, it is not easy to mix evenly.

[0010] As an optional embodiment, in the lithium iron phosphate slurry provided by the present invention, the thickener is selected from one or more of povidone, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose, and hydroxyethyl cellulose.

[0011] As an optional embodiment, in the lithium-rich lithium ferrite slurry provided by the present invention, the lithium-rich lithium ferrite is selected from one or both of pure lithium-rich lithium ferrite and carbon-coated lithium-rich lithium ferrite.

[0012] As an optional embodiment, in the lithium-rich lithium ferrite slurry provided by the present invention, the solvent is N-methylpyrrolidone.

[0013] Based on the same technical concept, the present invention also provides a method for preparing the above-mentioned lithium-rich lithium iron phosphate slurry, comprising the following steps: in a dry environment, weighing lithium-rich lithium iron phosphate powder, a thickener and a solvent in proportion, mechanically stirring the thickener to dissolve in the solvent, then adding the lithium-rich lithium iron phosphate and stirring under vacuum conditions to obtain a uniform suspension, and adjusting the viscosity to remove bubbles to obtain the lithium-rich lithium iron phosphate slurry.

[0014] As an optional embodiment, in the preparation method provided by the present invention, the viscosity of the lithium-rich lithium ferrite slurry is 6000-15000 mPa.s, and the slurry fineness is ≤30 μm.

[0015] As an optional embodiment, in the preparation method provided by the present invention, the environmental conditions are dew point ≤-40°C, and the vacuum degree during vacuum stirring is ≤-90kPa.

[0016] Based on the same technical concept, the present invention also provides the use of the above-mentioned lithium-rich lithium ferrite slurry as a lithium supplement in positive electrode slurry.

[0017] As an optional embodiment, in the application provided by the present invention, the method for using the lithium-rich lithium ferrite slurry is as follows: after the raw materials of the positive electrode material are dispersed, it is added before the step of adjusting the viscosity.

[0018] In the process of positive electrode slurrying, after other raw materials are dispersed, the prepared lithium-rich ferrite slurry is finally added, and the lithium-rich ferrite slurry is uniformly mixed with the positive electrode by mechanical stirring. The lithium-rich ferrite is used in the form of suspension slurry, which has better mixing effect, requires shorter mixing time, and reduces the possibility of PVDF gelation during slurrying.

[0019] As an optional implementation, in the application provided by the present invention, the mass ratio of the lithium-rich lithium ferrite slurry to the positive electrode active material is 0.5-5:100.

[0020] Furthermore, it is preferably 0.5-2:100.

[0021] Based on the same technical concept, the present invention also provides a positive electrode plate, which includes a positive electrode collector and a positive electrode membrane arranged on the positive electrode collector, and the positive electrode membrane contains the above-mentioned lithium iron-rich lithium slurry.

[0022] Based on the same technical concept, the present invention also provides a lithium-ion battery, comprising the above-mentioned positive electrode plate.

[0023] Compared with the prior art, the present invention has the following beneficial effects: (1) By making a stable slurry of lithium-rich iron oxide, solvent and thickener, the sensitivity of lithium-rich iron oxide to air and moisture is effectively reduced, the problem of easy failure of lithium-rich iron oxide is solved, and its use effect and convenience of storage and transportation are improved.

[0024] (2) In the present invention, the lithium iron-rich lithium oxide is added to the positive electrode slurry in the form of a suspension, which makes liquid mixing easier, reduces mixing time, and improves work efficiency.

[0025] (3) The present invention adds the lithium-rich lithium iron phosphate slurry in the last step of positive electrode slurry preparation, mixes evenly and then applies it, thereby avoiding the slurry gel problem during positive electrode slurry preparation caused by the premature reaction of the lithium-rich lithium iron phosphate with the binder PVDF in the positive electrode slurry, improving the stability of the positive electrode slurry, and thus improving the performance of the battery.

[0026] (4) The technical solution of the present invention has a simple process and low cost. Compared with the prior art, it not only saves energy and time in the preparation process, but also reduces production costs, and has high practical value. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 The present invention provides a preparation and application process of the lithium-rich lithium iron phosphate slurry; Figure 2 The charge and discharge curves of Example 1 and Comparative Examples 1-3 are shown; Figure 3 It is the charge and discharge curve diagram of Example 4 and Comparative Example 4. DETAILED DESCRIPTION

[0029] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0030] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0031] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0032] The preparation method of the lithium-rich lithium ferrite slurry proposed by the present invention is as follows: Figure 1 As shown, first, under dry conditions, lithium-rich iron phosphate powder, thickener and solvent are weighed in a certain proportion, the thickener is dissolved in the solvent by mechanical stirring, and then lithium-rich iron phosphate is added and stirred under vacuum conditions until a uniform suspension is obtained, and finally an appropriate amount of solvent NMP is added to make the slurry reach a suitable viscosity, and the bubbles generated by stirring are removed to obtain lithium-rich iron phosphate slurry. The application method of lithium-rich iron phosphate slurry is as follows Figure 1 As shown, the lithium iron oxide-rich slurry is added before the viscosity adjustment step of the positive electrode stirring, and after being evenly mixed, the viscosity is adjusted and bubbles are removed to obtain the positive electrode slurry with lithium iron oxide-rich added.

[0033] Example 1 (1) When the ambient dew point is ≤-40°C, prepare lithium-rich lithium ferrite, NMP and polyvidone (PVP), where the mass ratio of lithium-rich lithium ferrite: PVP: NMP is 90:10:50. Add the weighed NMP and PVP into the stirring kettle and stir until the PVP is completely dissolved.

[0034] (2) Add weighed lithium-rich iron oxide to a stirring kettle, stir under a vacuum condition of -90 kPa until the lithium-rich iron oxide is evenly dispersed, add an appropriate amount of NMP to make the slurry viscosity in the range of 8000-12000 mPa.s, and obtain a stable suspension of lithium-rich iron oxide after removing bubbles.

[0035] (3) According to the concentration of the prepared lithium-rich iron phosphate slurry, weigh the materials in the ratio of 2:100:1.2:2: lithium-rich iron phosphate: nickel cobalt manganese oxide (high voltage NCM523): conductive agent: binder. In the process of positive electrode slurry preparation, when the other raw materials are mixed evenly, the lithium-rich iron phosphate slurry is finally added, and the mixture is mechanically stirred in a double planetary stirring kettle to obtain a positive electrode slurry. After degassing and filtering, it is coated on the positive electrode current collector with a coater. Then, after drying, rolling and other processes, the positive electrode sheet is obtained. Keep a part of the positive electrode slurry, let it stand for 8 hours, and observe whether it is gelled. The obtained positive electrode sheet is assembled into a button battery with a lithium sheet as the negative electrode, and the specific capacity and initial efficiency tests are carried out. The results are shown in Table 1 and Figure 2 As shown, there is no gelation during the pulping process and when the slurry is left to stand for 8 hours. After deducting the charge capacity of the lithium nickel cobalt manganese oxide in Comparative Example 1, the charge capacity of the lithium iron oxide rich lithium is calculated to be 785 mAh / g.

[0036] Example 2 (1) When the ambient dew point is ≤-40°C, prepare lithium-rich lithium ferrite, NMP and ethyl cellulose (EC for short), where the mass ratio of lithium-rich lithium ferrite:EC is 97.5:2.5:80. Add the weighed NMP and EC into the double planetary stirred tank and stir until EC is completely dissolved.

[0037] (2) Add weighed lithium-rich ferrite into a stirring kettle and stir under a vacuum condition of -90 kPa until the lithium-rich ferrite is evenly dispersed. Add an appropriate amount of NMP to make the slurry viscosity in the range of 10000-15000 mPa.s. After removing bubbles, a stable suspension of the lithium supplement is obtained.

[0038] (3) According to the concentration of the prepared lithium-rich iron slurry, the materials are weighed in the ratio of 1.5:100:1.2:2 of lithium-rich iron slurry: nickel cobalt manganese oxide (high voltage NCM523): conductive agent: binder. In the process of positive electrode slurrying, when the other raw materials are mixed evenly, the lithium-rich iron slurry is finally added, and the mixture is mechanically stirred in a double planetary stirring kettle to obtain a positive electrode slurry with lithium-rich iron slurry added. After degassing and filtering, it is coated on the positive electrode current collector with a coating machine. Then, after drying, rolling and other processes, a positive electrode sheet is obtained. A portion of the positive electrode slurry is retained and left to stand for 8 hours to observe whether it is gelled. The obtained positive electrode sheet is assembled into a button battery with a lithium sheet as the negative electrode, and the specific capacity and first efficiency test are performed. The results are shown in Table 1. There is no gelation during the slurrying process and the slurry is left to stand for 8 hours. After deducting the charging specific capacity of the nickel cobalt manganese oxide in Comparative Example 1, the charging specific capacity of the lithium-rich iron slurry is calculated to be 793mAh / g.

[0039] Example 3 (1) When the ambient dew point is -40°C, prepare lithium-rich lithium ferrite, NMP and hydroxypropyl methylcellulose (HPMC), where the mass ratio of lithium-rich lithium ferrite: HPMC: NMP is 98.5:1.5:100. Add the weighed NMP and HPMC into the stirring kettle and stir until HPMC is completely dissolved in NMP.

[0040] (2) Add weighed lithium-rich nickel oxide into a stirring kettle and stir under a vacuum condition of -90 kPa until the lithium-rich lithium iron oxide is evenly dispersed. Add an appropriate amount of NMP to make the slurry viscosity in the range of 6000-10000 mPa.s. After removing bubbles, a stable suspension of the lithium supplement is obtained.

[0041] (3) According to the concentration of the prepared lithium-rich iron slurry, the materials are weighed in the ratio of lithium-rich iron slurry: nickel cobalt manganese oxide (high voltage NCM523): conductive agent: binder of 1.0:100:1.2:2. In the process of positive electrode slurrying, when the other raw materials are mixed evenly, the lithium-rich iron slurry is finally added, and the mixture is mechanically stirred in a double planetary stirring kettle to obtain a positive electrode slurry with lithium-rich nickel oxide added. After degassing and filtering, it is coated on the positive electrode current collector with a coating machine. Then, after drying, rolling and other processes, a positive electrode sheet is obtained. A portion of the positive electrode slurry is retained and left to stand for 8 hours to observe whether it is gelled. The obtained positive electrode sheet is assembled into a button battery with a lithium sheet as the negative electrode, and the specific capacity and first efficiency test are performed. The results are shown in Table 1. There is no gelation during the slurrying process and the slurry is left to stand for 8 hours. After deducting the charging specific capacity of the nickel cobalt manganese oxide in Comparative Example 1, the charging specific capacity of the lithium-rich iron slurry is calculated to be 780mAh / g.

[0042] Example 4 (1) When the ambient dew point is ≤-40°C, prepare lithium supplement carbon-coated lithium-rich ferrite (carbon content 2%), NMP and hydroxyethyl cellulose (HEC), where the mass ratio of lithium-rich ferrite: HEC: NMP is 98:2:100. Add the weighed NMP and PVP and stir until the PVP is completely dissolved.

[0043] (2) Add weighed lithium-rich ferrite into a stirring kettle, stir under a vacuum condition of -90 kPa until the lithium-rich ferrite is evenly dispersed, add an appropriate amount of NMP to make the slurry viscosity in the range of 6000-12000 mPa.s, and obtain a stable suspension of the lithium supplement after removing bubbles.

[0044] (3) According to the concentration of the prepared lithium-rich iron phosphate slurry, weigh the materials in the ratio of 2:100:1.2:2 of lithium-rich iron phosphate: lithium iron phosphate: conductive agent: binder. In the process of positive electrode slurry preparation, after the other raw materials are evenly mixed, finally add the lithium-rich iron phosphate slurry, and mix by mechanical stirring in a double planetary stirring kettle to obtain positive electrode slurry. After degassing and filtering, use a coater to coat it on the positive electrode current collector. Then after drying, rolling and other processes, the positive electrode sheet is obtained. Keep a part of the positive electrode slurry, let it stand for 8 hours, and observe whether it is gelled. The obtained positive electrode sheet is assembled into a button battery with the lithium sheet as the negative electrode, and the specific capacity and initial efficiency tests are carried out. The results are shown in Table 1 and Figure 3 As shown, there is no gelation during the pulping process and when the slurry is left to stand for 8 hours. After deducting the charge capacity of lithium iron manganese phosphate in Comparative Example 1, the charge capacity of lithium iron oxide rich in lithium is calculated to be 785 mAh / g.

[0045] Comparative Example 1 The ambient dew point is ≤-40℃, and the materials are weighed in a ratio of 100:1.2:2 of lithium nickel cobalt manganese oxide (high voltage NCM523): conductive agent: binder. Use a double planetary stirring kettle to mix by mechanical stirring in sequence to obtain positive electrode slurry. After degassing and filtering, use a coater to apply it to the positive electrode collector. Then after drying, rolling and other processes, the positive electrode sheet is obtained. Keep part of the positive electrode slurry, let it stand for 8 hours, and observe whether it is gelled. The obtained positive electrode sheet is assembled into a button battery with a lithium sheet as the negative electrode, and the specific capacity and initial efficiency tests are carried out. The results are shown in Table 1 and Figure 2 The slurry making process and the slurry standing for 8 hours did not gel. The specific charge capacity of lithium nickel cobalt manganese oxide is 221.7 mAh / g, and the specific discharge capacity is 197.9 mAh / g.

[0046] Comparative Example 2 The ambient dew point is ≤-40℃. Prepare lithium supplement lithium-rich ferrite powder (Li5FeO4). Weigh the materials according to the ratio of 2:100:1.2:2 of lithium-rich ferrite: nickel cobalt manganese oxide (high voltage NCM523): conductive agent: binder. Use a double planetary stirring kettle to mix mechanically. After the binder dispersion and conductive agent dispersion steps are carried out in sequence, lithium-rich ferrite powder is added for dispersion. Finally, nickel cobalt manganese oxide is added for dispersion to obtain a positive electrode slurry. After degassing and filtering, apply it to the positive electrode current collector with a coater. Then, after drying, rolling and other processes, a positive electrode sheet is obtained. Keep a part of the positive electrode slurry, let it stand for 8 hours, and observe whether it is gelled. The obtained positive electrode sheet is assembled into a button battery with a lithium sheet as the negative electrode, and the specific capacity and first efficiency tests are carried out. The results are shown in Table 1 and Figure 2 , gelation occurs during the pulping process, and gelation becomes more serious after standing. After deducting the charge capacity of the nickel cobalt manganese oxide in Comparative Example 1, the charge capacity of the lithium iron oxide rich lithium is calculated to be 680 mAh / g, which is significantly lower than the result of the embodiment.

[0047] Comparative Example 3 The ambient dew point is ≤-40℃. Prepare lithium supplement carbon-coated lithium-rich iron phosphate powder (carbon content is 2%). Weigh the materials according to the ratio of carbon-coated lithium-rich iron phosphate: nickel cobalt manganese oxide (high voltage NCM523): conductive agent: binder of 2:100:1.2:2. Use a double planetary stirring kettle to mix mechanically. After the binder dispersion and conductive agent dispersion steps are carried out in sequence, add the carbon-coated lithium-rich iron phosphate powder for dispersion, and finally add nickel cobalt manganese oxide to disperse to obtain the positive electrode slurry. After degassing and filtering, use a coater to coat it on the positive electrode current collector. Then, after drying, rolling and other processes, the positive electrode sheet is obtained. Keep part of the positive electrode slurry, let it stand for 8 hours, and observe whether it is gelled. The obtained positive electrode sheet is assembled into a button battery with the lithium sheet as the negative electrode, and the specific capacity and first efficiency tests are carried out. The results are shown in Table 1 and Figure 3 The slurry preparation process and the slurry standing for 8 hours did not gel. After deducting the charge capacity of the nickel cobalt manganese oxide in Comparative Example 1, the charge capacity of the lithium iron oxide rich lithium was calculated to be 750 mAh / g, which is lower than the result of the embodiment.

[0048] Comparative Example 4 The ambient dew point is ≤-40℃, and the materials are weighed in a ratio of 100:1.2:2 for lithium manganese iron phosphate: conductive agent: binder. Use a double planetary stirring kettle to disperse the binder, conductive agent and positive electrode material in turn to obtain positive electrode slurry. After degassing and filtering, use a coater to apply it to the positive electrode collector. Then, after drying, rolling and other processes, the positive electrode sheet is obtained. Keep a part of the positive electrode slurry, let it stand for 8 hours, and observe whether it is gelled. The obtained positive electrode sheet is assembled into a button battery with a lithium sheet as the negative electrode, and the specific capacity and initial efficiency tests are carried out. The results are shown in Table 1 and Figure 3There was no gelation during the pulping process and when the slurry was left to stand for 8 hours. The specific charge capacity of lithium manganese iron phosphate was 165.2 mAh / g, and the specific discharge capacity was 159.4 mAh / g.

[0049] The test results are shown in Table 1 below.

[0050] Table 1: Test results of embodiments and comparative examples

[0051] The specific capacity of lithium-rich iron oxide is calculated based on the first charge specific capacity and the first discharge specific capacity. Figure 2 It can be seen that the specific capacities of lithium-rich ferrite in Examples 1-3 are all above 780 mAh / g, which is significantly higher than the result of 680 mAh / g in Comparative Example 2, which directly uses lithium-rich ferrite powder. This shows that using lithium-rich ferrite in the form of slurry can significantly improve the failure of lithium-rich ferrite in contact with air and moisture. The specific charging capacity of lithium-rich ferrite in Comparative Example 3 is 750 mAh / g, which proves that the effect of using lithium-rich ferrite slurry is slightly better than directly using carbon-coated lithium-rich ferrite. From Tables 1 and Figure 3 It can be seen that the lithium-rich lithium iron phosphate slurry prepared by the present invention has strong adaptability to positive electrode materials and can also play a good role in lithium iron manganese phosphate positive electrodes. Compared with Example 4 and Comparative Example 4, the use of lithium-rich lithium iron phosphate in the form of slurry can significantly improve the specific charge capacity in lithium iron manganese phosphate batteries. The slurry gel experiment results show that the positive electrode slurry does not gel during the slurrying and 8h standing process using the lithium-rich lithium iron phosphate slurry of the present invention, proving that the present invention has an obvious improvement effect on the positive electrode slurry gel caused by lithium-rich lithium iron phosphate.

[0052] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.

Claims

1. A lithium-rich lithium iron phosphate slurry, characterized in that: The invention is composed of lithium-rich lithium ferrate, a thickener and a solvent, wherein the solvent is the solvent used in preparing the positive electrode slurry.

2. The lithium-rich lithium iron slurry according to claim 1, characterized in that: The mass ratio of the lithium-rich lithium ferrite, the thickener and the solvent is 90-99.5:0.5-10:25-200.

3. The lithium-rich lithium ferrite slurry according to claim 1, characterized in that: The thickener is selected from one or more of povidone, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose, and hydroxyethyl cellulose; the lithium ferrite-rich is selected from one or both of pure lithium ferrite-rich and carbon-coated lithium ferrite-rich.

4. The method for preparing the lithium-rich lithium ferrite slurry according to any one of claims 1 to 3, characterized in that: The following steps are involved: In a dry environment, lithium-rich lithium ferrite powder, a thickener and a solvent are weighed in proportion, the thickener is mechanically stirred to dissolve in the solvent, and then the lithium-rich lithium ferrite is added and stirred under vacuum conditions to obtain a uniform suspension. After adjusting the viscosity and removing bubbles, lithium-rich lithium ferrite slurry is obtained.

5. The method for preparing lithium-rich lithium ferrite slurry according to claim 4, characterized in that: The viscosity of the lithium-rich lithium ferrite slurry is 6000-15000 mPa.s, and the slurry fineness is ≤30 μm.

6. The method for preparing lithium-rich lithium ferrite slurry according to claim 4, characterized in that: The environmental condition is that the dew point is ≤-40°C, and the vacuum degree during the vacuum stirring is ≤-90kPa.

7. Use of the lithium-rich lithium ferrite slurry as claimed in any one of claims 1 to 3 as a lithium supplement in a positive electrode slurry.

8. The use according to claim 7, characterized in that: The method for using the lithium-rich lithium ferrite slurry is as follows: adding the lithium-rich lithium ferrite slurry after the raw materials of the positive electrode material are dispersed and before the viscosity adjustment step; the mass ratio of the lithium-rich lithium ferrite slurry to the positive electrode active material is 0.5-5:

100.

9. A positive electrode sheet, characterized in that: The positive electrode plate comprises a positive electrode current collector and a positive electrode membrane arranged on the positive electrode current collector, and the positive electrode membrane contains the lithium-rich lithium ferrite slurry as described in any one of claims 1 to 3.

10. A lithium ion battery, characterized in that: Including the positive electrode sheet as described in claim 9.

Citation Information

Patent Citations

  • Lithium ion battery diaphragm and preparation method thereof

    CN110571395A

  • Preparation method of lithium supplementing conductive slurry, lithium supplementing conductive paste, lithium ion battery and electronic equipment

    CN112447963A

  • Lithium supplement agent, lithium supplement method, positive plate, lithium supplement slurry and battery for positive electrode of lithium ion battery

    CN114824168A

  • Positive electrode lithium supplementing slurry, preparation method and application thereof, and lithium ion battery

    CN116207264A

  • Lithium iron phosphate graphene composite anode lithium-rich coating and preparation method thereof

    CN117334843A

Cited By

  • High-tap-density ferric sodium pyrophosphate positive electrode material as well as preparation method and application thereof

    CN121134716A